2021
DOI: 10.1186/s12885-020-07775-4
|View full text |Cite
|
Sign up to set email alerts
|

Advance directives and end-of-life care: knowledge and preferences of patients with brain Tumours from Anhui, China

Abstract: Background In Mainland China, advance directives (ADs) and end-of-life care for patients with tumours, especially patients with brain tumours who may have lost consciousness or the ability to speak at the early stage of their illness, have been poorly acknowledged. Thus, this study aimed to clarify the knowledge and preferences of ADs and end-of-life care in patients with brain tumours and to investigate predictors of patient preferences. Methods T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
31
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 32 publications
2
31
0
4
Order By: Relevance
“…In addition, The study indicated that relatively few aged citizens completed the forms due to lacing Internet technology abilities as the ‘Five Wishes’ forms were online and digital [ 24 ]. Furthermore, Chinese scholars conducted cross-sectional studies on the recognition, acceptance, knowledge, attitude and practice (KAP) of ADs using self-designed questionnaires among terminally ill patients, older adults and health professionals [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ]. Overall, the recognition, acceptance, knowledge and KAP of ADs among the population improved over time [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, The study indicated that relatively few aged citizens completed the forms due to lacing Internet technology abilities as the ‘Five Wishes’ forms were online and digital [ 24 ]. Furthermore, Chinese scholars conducted cross-sectional studies on the recognition, acceptance, knowledge, attitude and practice (KAP) of ADs using self-designed questionnaires among terminally ill patients, older adults and health professionals [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ]. Overall, the recognition, acceptance, knowledge and KAP of ADs among the population improved over time [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Chinese scholars conducted cross-sectional studies on the recognition, acceptance, knowledge, attitude and practice (KAP) of ADs using self-designed questionnaires among terminally ill patients, older adults and health professionals [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ]. Overall, the recognition, acceptance, knowledge and KAP of ADs among the population improved over time [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ]. And health care professionals had a higher recognition and acceptance of ADs, better KAP of ADs compared with the other groups at the same time period [ [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, nudges from sending letters, texts, and messages through patient portals are frequently used and have been effective in increasing cervical cancer screening (Tseng et al, 2001), medication adherence (Schwebel & Larimer, 2018), appointment attendance (Horvath et al, 2011; Schwebel & Larimer, 2018), and most recently, vaccine uptake (Dai et al, 2021; Patel et al, 2023). Previous studies on patient-side interventions in ACP have involved improving patients’ knowledge of ADs in China (Wang et al, 2021), using an online tool to guide patients through ACP during the coronavirus pandemic (Auriemma et al, 2020), and educating patients in a small inpatient setting to improve AD completion (Harlow, 2017). We add to the growing behavioral health economics literature on nudges, letters, and reminders, showing in a randomized control trial that interventions with nudges and various communications, especially when tied to physician appointments, are effective in increasing the take-up of beneficial but also potentially frustrating responsibilities such as completing ADs.…”
Section: Introductionmentioning
confidence: 99%
“…6,47,48 Chinese patients prefer to be informed and engage in shared discussions with important ones and only a small number wanted to be in control of important medical decisions. [49][50][51] Chinese patients' preferences regarding the level of involvement in medical decision-making practices may vary at different stages. Our findings suggest that most family caregivers prefer to start discussing life-sustaining treatments only when the patient is seriously ill, because they do not want the patient to lose hope too early, in which case patients' opportunities to participate in the decision-making process may be reduced by the late initiation.…”
mentioning
confidence: 99%